Pengaruh Pemasaran Digital dan Suasana Toko Terhadap Minat Beli di Kaca Coffee and Eatery - Nadya Rachel; Donant Alananto Iskandar (UNIVERSITAS KALBIS, 2022)
This study aims to analyze the influence of digital marketing and store atmosphere on buying interest in KACA Coffee and Eatery. Sources of data were obtained from observations on Glass Coffee and Eatery in May 2019. The method used was descriptive method by distributing questionnaires through Google Form, then processed using IBM SPSS Statistics application. Based on 105 respondents who have come to KACA Coffee and Eatery and have accessed the KACA Coffee and Eatery Instagram. The results show that digital marketing and store atmosphere affect buying interest. The accepted hypothesis was decided based on the results of the t value analysis. It can be concluded that KACA Coffee and Eatery need to improve promotion through social media so that consumers can consider more about coming to KACA Coffee and Eatery